Transparent conductive film

The transparent conductive film, featuring an amorphous indium tin composite oxide layer and a polyethylene terephthalate substrate, addresses the challenge of maintaining flexibility after heating by achieving a balanced heat shrinkage rate and low resistance.

JP2025053965APending Publication Date: 2025-04-07NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023163107
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

Existing transparent conductive films face challenges in maintaining flexibility after heating, as the crystallization of the conductive layer reduces flexibility and high heat shrinkage rates are not achieved.

Method used

A transparent conductive film with an amorphous transparent conductive layer made of indium tin composite oxide, having a thickness of 100 nm or more, and a heat shrinkage rate of 0.40% or more but less than 1.50% after heating, is used. The film is supported by a polyethylene terephthalate substrate, ensuring improved flexibility and resistance.

Benefits of technology

The film achieves low resistance and significantly improved flexibility after heating, with a heat shrinkage rate within the desired range, ensuring excellent mechanical properties and transparency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025053965000001_ABST
    Figure 2025053965000001_ABST
Patent Text Reader

Abstract

To provide a transparent conductive film which is low resistive, and has improved flexibility after heating compared with flexibility before heating, and is excellent in flexibility after heating.SOLUTION: A transparent conductive film 1 has a first direction where a thermal shrinkage in a surface direction orthogonal to a thickness direction by heat treatment of a heating condition of 140°C for 30 min. is maximum. The transparent conductive film includes: a transparent substrate 10; and a transparent conductive layer 20 disposed on one surface in a thickness direction of the transparent substrate 10, where the transparent conductive layer 20 is amorphous, the thickness of the transparent conductive layer 20 is 100 nm or thicker. The transparent conductive layer 20 after heat-treating the transparent conductive film 1 by the above heating condition is amorphous, and the thermal shrinkage in a first direction after heat-treating the transparent conductive film 1 by the above heating condition is 0.40% or more and less than 1.50%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent conductive film. [Background technology]

[0002] Conventionally, a transparent conductive film has been known that includes a transparent resin substrate film and a transparent conductive layer in that order in the thickness direction. Such a transparent conductive layer is made of indium tin oxide (ITO) and is used to form a pattern of transparent electrodes in various devices such as liquid crystal displays, touch panels, and optical sensors.

[0003] In the process of forming the transparent conductive layer, for example, first, an amorphous film of a transparent conductive material is formed on a substrate film by a sputtering method (film formation process). Next, the amorphous transparent conductive layer on the substrate film is crystallized by heating (crystallization process). Such technology related to the transparent conductive film is described, for example, in Patent Document 1 below. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-71850 A Summary of the Invention [Problem to be solved by the invention]

[0005] On the other hand, assuming that the transparent conductive film has low resistance, from the viewpoint of ensuring the quality, it is preferable that the flexibility after heating is improved compared to the flexibility before heating. Furthermore, it is desirable that the flexibility of the transparent conductive film after heating is excellent.

[0006] However, the transparent conductive film of Patent Document 1 has a drawback in that the flexibility after heating is reduced compared to the flexibility before heating, since the transparent conductive layer is crystallized by heating.

[0007] Even if the transparent conductive layer is not crystallized by heating, if the maximum thermal shrinkage of the transparent conductive film in the plane direction perpendicular to the thickness direction is low, there is a problem in that the flexibility after heating is poor.

[0008] An object of the present invention is to provide a transparent conductive film which has low resistance and further has excellent flexibility after heating, that is, flexibility after heating is improved compared to the flexibility before heating. [Means for solving the problem]

[0009] The present invention [1] provides a transparent conductive film having a first direction in which a thermal shrinkage rate due to heat treatment under heating conditions of 140°C for 30 minutes is maximum in a plane direction perpendicular to the thickness direction, the transparent conductive film comprising a transparent substrate and a transparent conductive layer disposed on one surface in the thickness direction of the transparent substrate, the transparent conductive layer being amorphous and having a thickness of 100 nm or more, and the transparent conductive layer being amorphous, and the thermal shrinkage rate of the transparent conductive film in the first direction after heat treatment under the heating conditions is 0.40% or more and less than 1.50%.

[0010] The present invention [2] includes the transparent conductive film according to [1], in which the transparent conductive layer has a thickness of 300 nm or less.

[0011] The present invention [3] includes the transparent conductive film according to [1] or [2], in which the transparent substrate is a polyethylene terephthalate film.

[0012] The present invention [4] includes the transparent conductive film according to any one of [1] to [3], in which the transparent conductive layer contains an indium tin composite oxide.

[0013] The present invention [5] includes the transparent conductive film according to [4], in which the content of tin oxide in the indium tin composite oxide relative to the total content of indium oxide and tin oxide is 10 mass% or more. Effect of the Invention

[0014] The transparent conductive film of the present invention has a low resistance because the transparent conductive layer has a thickness of 100 nm or more. In addition, the transparent conductive film of the present invention has an amorphous transparent conductive layer after heat treatment, so that the flexibility after heating is improved compared to the flexibility before heating. Furthermore, the thermal shrinkage in the first direction after heat treatment is 0.40% or more and less than 1.50%, so that the flexibility after heating is excellent. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 shows a cross-sectional view of one embodiment of the transparent conductive film of the present invention. [Diagram 2] Fig. 2 shows a method for producing the transparent conductive film shown in Fig. 1. Fig. 2A shows a step of preparing a transparent substrate, and Fig. 2B shows a step of forming a transparent conductive layer on the transparent substrate. [Diagram 3] FIG. 3 shows a bending test of the transparent conductive films of the examples and the comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] <Transparent conductive film> One embodiment of the transparent conductive film of the present invention will be described with reference to FIG.

[0017] The transparent conductive film 1 has a film shape (including a sheet shape) with a predetermined thickness, as shown in Fig. 1. The transparent conductive film 1 extends in a plane direction perpendicular to the thickness direction, and one surface (upper surface) and the other surface (lower surface) in the thickness direction of the transparent conductive film 1 are flat.

[0018] The transparent conductive film 1 has a first direction in which the thermal shrinkage rate is maximum when heated for 30 minutes at 140° C. in the planar direction. The transparent conductive film 1 also has a second direction perpendicular to the first direction.

[0019] The first direction in the plane of the transparent conductive film 1 (the direction in which the thermal shrinkage rate due to the heat treatment under the above heating conditions is maximum) can be specified by the method described in the examples below.

[0020] 1, the transparent conductive film 1 includes a transparent substrate 10 and a transparent conductive layer 20 in this order. Specifically, the transparent conductive film 1 includes the transparent substrate 10 and the transparent conductive layer 20 disposed on one surface (upper surface) of the transparent substrate 10 in the thickness direction. The transparent conductive film 1 preferably includes only the transparent substrate 10 and the transparent conductive layer 20 disposed on one surface (upper surface) of the transparent substrate 10 in the thickness direction.

[0021] [Transparent base material] The transparent substrate 10 is the bottom layer of the transparent conductive film 1 and is a supporting material that ensures the mechanical strength of the transparent conductive film 1. The transparent substrate 10 is also a flexible, transparent supporting material. The transparent substrate 10 supports the transparent conductive layer 20.

[0022] The transparent substrate 10 has a film shape (including a sheet shape).

[0023] The transparent substrate 10 includes, for example, a transparent resin film having flexibility, and is preferably a transparent resin film having flexibility.

[0024] Examples of materials for the resin film include polyester resins such as polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate; (meth)acrylic resins (acrylic resin and / or methacrylic resin) such as polymethacrylate; olefin resins such as polyethylene, polypropylene, and cycloolefin polymer; polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, cellulose resin, polystyrene resin, and norbornene resin.

[0025] From the viewpoints of flexibility, heat resistance, mechanical strength, etc., the resin film is preferably a polyester-based film formed from a polyester resin, more preferably a polyethylene terephthalate film. That is, the transparent substrate 10 is, for example, a polyethylene terephthalate film.

[0026] These polymer films can be used alone or in combination of two or more kinds.

[0027] Examples of the transparent substrate 10 include a non-stretched film, a uniaxially stretched film, and a biaxially stretched film, and preferably a biaxially stretched film.

[0028] The transparent substrate 10 is, for example, a film that has been heat-treated in an atmospheric environment, and is preferably a biaxially stretched film that has been heat-treated in an atmospheric environment.

[0029] If the transparent substrate 10 is a biaxially stretched film that has been heat-treated in an atmospheric environment, the stress present inside the transparent substrate 10 is alleviated, and therefore, when the transparent conductive film 1 is heated, excessive shrinkage of the transparent substrate 10 can be suppressed, and the occurrence of cracks in the transparent conductive layer 20 can be suppressed.

[0030] One surface in the thickness direction of the transparent substrate 10 (the surface on the transparent conductive layer 20 side) may be subjected to a surface modification treatment. Examples of the surface modification treatment include a corona treatment, a plasma treatment, an ozone treatment, a primer treatment, a glow treatment, and a coupling agent treatment.

[0031] The surface roughness Ra (arithmetic mean surface roughness) of one surface in the thickness direction of the transparent substrate 10 (the surface on the transparent conductive layer 20 side) is, for example, 0.5 nm to 30 nm, preferably 1 nm to 20 nm, more preferably 2 nm to 15 nm, even more preferably 3 nm to 12 nm, particularly preferably 4 nm to 10 nm, and most preferably 5 nm to 8 nm.

[0032] The surface roughness Ra of one surface in the thickness direction of the transparent substrate 10 can be determined, for example, from an observation image of an area of ​​1 μm square using an AFM (atomic force microscope).

[0033] If the surface roughness of one surface in the thickness direction of the transparent substrate 10 (the surface on the transparent conductive layer 20 side) is within the above range, crystallization of the transparent conductive layer 20 can be suppressed when the transparent conductive film 1 is heated. Therefore, the amorphous nature of the transparent conductive layer 20 can be maintained. The surface roughness of one surface in the thickness direction of the transparent substrate 10 (the surface on the transparent conductive layer 20 side) can be appropriately adjusted by the heating conditions of the transparent conductive film 1, etc.

[0034] The total light transmittance (JISK-7105) of the transparent substrate 10 is, for example, 80% to 100%, preferably 85% to 100%, and more preferably 88% to 100%.

[0035] If the total light transmittance of the transparent substrate 10 is within the above range, the transparency of the transparent conductive film 1 can be ensured.

[0036] The haze (JISK-7105) of the transparent substrate 10 is, for example, 0.1% to 2.0%, preferably 0.1% to 1.8%, more preferably 0.1% to 1.5%, and still more preferably 0.1% to 1.2%.

[0037] If the haze of the transparent substrate 10 is within the above range, the transparency of the transparent conductive film 1 can be ensured.

[0038] The transparent substrate 10 has a thickness of, for example, 20 μm or more, preferably 50 μm or more, more preferably 100 μm or more, even more preferably 130 μm or more, particularly preferably 150 μm or more, and most preferably 175 μm or more.

[0039] The lower limit of the thickness of the transparent substrate 10 can be appropriately adjusted depending on the heating conditions of the transparent conductive film 1. Specifically, when the transparent substrate 10 is thick, more moisture contained in the polymer film is imparted to the transparent conductive layer 20 when the transparent conductive film 1 is heated, so that crystallization of the transparent conductive layer 20 is suppressed and the amorphous nature is maintained.

[0040] Furthermore, when the thickness of the transparent substrate 10 is equal to or greater than the above lower limit, the strength of the transparent conductive film 1 is excellent.

[0041] The transparent substrate 10 has a thickness of, for example, 500 μm or less, preferably 400 μm or less, more preferably 300 μm or less, still more preferably 250 μm or less, and particularly preferably 200 μm or less.

[0042] When the thickness of the transparent substrate 10 is equal to or less than the above upper limit, the thickness of the transparent conductive film 1 can be prevented from becoming excessively thick, and therefore the transparent conductive film 1 has excellent flexibility before heating.

[0043] The transparent substrate 10 has a thickness of, for example, 20 μm to 500 μm, preferably 50 μm to 400 μm, more preferably 100 μm to 300 μm, still more preferably 130 μm to 250 μm, particularly preferably 150 μm to 200 μm, and most preferably 175 μm to 200 μm.

[0044] The thickness of the transparent substrate 10 can be measured, for example, by using a thickness meter.

[0045] The transparent substrate 10 may have a functional layer (not shown) on one side (one side in the thickness direction or the other side in the thickness direction) or on both sides (one side in the thickness direction and the other side in the thickness direction) of the resin film, as necessary.

[0046] Examples of the functional layer include a hard coat layer, an anti-blocking layer, and an optical adjustment layer. The hard coat layer, for example, makes the exposed surface of the transparent conductive layer 20 less susceptible to scratches. The anti-blocking layer imparts blocking resistance to the surfaces of the transparent conductive films 1 that are in contact with each other, for example, when the transparent conductive films 1 are laminated in the thickness direction. The optical adjustment layer adjusts the reflectance of the surface (one surface in the thickness direction) of the transparent substrate 10.

[0047] An example of the functional layer is a cured resin layer. The cured resin layer is, for example, a cured product of a curable resin composition. The curable resin composition contains a curable resin. Examples of the curable resin include polyester resin, acrylic urethane resin, acrylic resin (excluding acrylic urethane resin), urethane resin (excluding acrylic urethane resin), amide resin, silicone resin, epoxy resin, and melamine resin. The curable resin can be used alone or in combination of two or more kinds. Examples of the curable resin include ultraviolet curable resin and thermosetting resin.

[0048] The curable resin composition may contain particles. Examples of the particles include inorganic oxide particles and organic particles. Examples of the inorganic oxide particle material include silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide. Examples of the organic particle material include polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate.

[0049] The thickness of the cured resin layer is, for example, 0.1 μm to 10 μm, preferably 0.5 μm to 5 μm, and more preferably 1 μm to 3 μm.

[0050] When the thickness of the cured resin layer is equal to or less than the upper limit, it is possible to ensure the transparency of the transparent conductive film 1. When the thickness of the cured resin layer is equal to or more than the lower limit, it is possible to fully exhibit the function of the cured resin layer in the transparent conductive film 1.

[0051] [Transparent conductive layer] The transparent conductive layer 20 has both transparency and conductivity. The transparent conductive layer 20 is disposed on one surface in the thickness direction of the transparent substrate 10. Specifically, the transparent conductive layer 20 contacts one surface of the transparent substrate 10 in the thickness direction.

[0052] The transparent conductive layer 20 includes, for example, a conductive oxide.

[0053] Examples of the conductive oxide include metal oxides containing at least one metal or semimetal selected from the group consisting of In, Sn, Zn, Ga, Sb, Ti, Si, Zr, Mg, Al, Au, Ag, Cu, Pd, and W, and preferably include indium-containing conductive oxides and antimony-containing conductive oxides. Examples of the indium-containing conductive oxide include indium tin composite oxide (ITO), indium zinc composite oxide (IZO), indium gallium composite oxide (IGO), and indium gallium zinc composite oxide (IGZO). Examples of the antimony-containing conductive oxide include antimony tin composite oxide (ATO). From the viewpoint of achieving high transparency and good electrical conductivity, more preferably, the conductive oxide is an indium-containing conductive oxide, and even more preferably, an indium tin composite oxide (ITO) containing both In and Sn. That is, the transparent conductive layer 20 preferably includes indium tin composite oxide (ITO). ITO may contain a metal or semi-metal other than In and Sn in an amount less than the respective contents of In and Sn.

[0054] When ITO is used as the conductive oxide, the ratio of the tin oxide content to the total content of indium oxide (In2O3) and tin oxide (SnO2) in the ITO is, for example, 1.0 mass% or more, preferably 3.0 mass% or more, more preferably 5.0 mass% or more, even more preferably 7.0 mass% or more, particularly preferably 10.0 mass% or more, and most preferably 12.0 mass% or more.

[0055] If the ratio of the content of tin oxide to the total content of indium oxide (In2O3) and tin oxide (SnO2) in ITO is equal to or greater than the above lower limit, the durability of the transparent conductive layer 20 can be ensured.

[0056] The ratio of the tin oxide content to the total content of indium oxide (In2O3) and tin oxide (SnO2) in ITO is, for example, 20.0 mass % or less, preferably 18.0 mass % or less, and more preferably 15.0 mass % or less.

[0057] The ratio of the tin oxide content to the total content of indium oxide (In2O3) and tin oxide (SnO2) in ITO is, for example, 1.0 mass% to 20.0 mass%, preferably 3.0 mass% to 18.0 mass%, more preferably 5.0 mass% to 15.0 mass%, even more preferably 7.0 mass% to 15.0 mass% or more, particularly preferably 10.0 mass% to 15.0 mass%, and most preferably 12.0 mass% to 15.0 mass%.

[0058] The ratio of the number of tin atoms to the number of indium atoms in ITO (number of tin atoms / number of indium atoms) is, for example, 0.01 to 0.25, preferably 0.02 to 0.21, more preferably 0.05 to 0.17, still more preferably 0.07 to 0.17, particularly preferably 0.10 to 0.17, and most preferably 0.12 to 0.17.

[0059] The ratio of the number of tin atoms to the number of indium atoms in ITO can be determined, for example, by determining the abundance ratio of indium atoms and tin atoms in the measurement object by X-ray photoelectron spectroscopy. The above-mentioned content ratio of tin oxide in ITO can be determined, for example, from the abundance ratio of indium atoms and tin atoms thus determined. The above-mentioned content ratio of tin oxide in ITO may be determined from the content ratio of tin oxide (SnO2) in the ITO target used during sputtering film formation.

[0060] The transparent conductive layer 20 is amorphous. If the transparent conductive layer 20 is amorphous, it has excellent flexibility and scratch resistance before heating, and therefore excellent processability.

[0061] Moreover, the amorphous transparent conductive layer 20 does not change to a crystalline state by heating. Specifically, the transparent conductive layer 20 is amorphous after the transparent conductive film 1 is heat-treated at 140° C. for 30 minutes. If the transparent conductive layer 20 is amorphous after the transparent conductive film 1 is heat-treated at 140° C. for 30 minutes, the flexibility after heating is improved compared to the flexibility before heating.

[0062] The fact that the transparent conductive layer 20 is amorphous can be determined by observing a cross section of the transparent conductive layer 20 with a field emission transmission electron microscope (FE-TEM). When no crystal grains are observed but an amorphous region is observed in the cross section of the transparent conductive layer 20 with the FE-TEM, it can be determined that the transparent conductive layer 20 is amorphous.

[0063] The transparent conductive layer 20 has a thickness of 100 nm or more, preferably 110 nm or more, and more preferably 120 nm or more.

[0064] When the thickness of the transparent conductive layer 20 is equal to or greater than the above lower limit, the resistance value (surface resistance) of the transparent conductive layer 20 can be reduced.

[0065] The transparent conductive layer 20 has a thickness of, for example, 500 nm or less, preferably 300 nm or less, more preferably 250 nm or less, still more preferably 200 nm or less, and particularly preferably 150 nm or less.

[0066] When the thickness of the transparent conductive layer 20 is equal to or less than the above upper limit, it is possible to prevent cracks from occurring in the transparent conductive layer 20 when the transparent conductive film 1 is bent after heating, that is, the film has excellent bendability after heating.

[0067] The transparent conductive layer 20 has a thickness of, for example, 100 nm to 500 nm, preferably 100 nm to 300 nm, more preferably 110 nm to 250 nm, still more preferably 110 nm to 200 nm, and particularly preferably 120 nm to 150 nm.

[0068] The ratio of the thickness of the transparent conductive layer 20 to the thickness of the transparent substrate 10 (thickness of the transparent conductive layer 20 / thickness of the transparent substrate 10) is, for example, 0.3×10 -3 ~1.5×10 -3 , preferably 0.4 x 10 -3 ~1.2×10 -3 , more preferably 0.4×10 -3 ~1.0×10 -3 , more preferably 0.5×10 -3 ~0.8×10 -3 , particularly preferably 0.6×10 -3 ~0.7×10 -3 It is.

[0069] The transparent conductive layer 20 has a total light transmittance (JIS K 7375-2008) of, for example, 60% to 100%, preferably 80% to 100%, more preferably 85% to 100%, and still more preferably 88% to 100%.

[0070] If the total light transmittance of the transparent conductive layer 20 is within the above range, the transparency required of the transparent conductive film 1 can be ensured when the transparent conductive film 1 is used in touch sensor devices, dimming elements, photoelectric conversion elements, heat ray control components, antenna components, electromagnetic wave shielding components, heater components, lighting devices, image display devices, and the like.

[0071] The resistance value (surface resistance) of the transparent conductive layer 20 is, for example, 0 Ω / □ to 250 Ω / □, preferably 0 Ω / □ to 200 Ω / □, more preferably 0 Ω / □ to 150 Ω / □, even more preferably 0 Ω / □ to 100 Ω / □, particularly preferably 0 Ω / □ to 80 Ω / □, and most preferably 0 Ω / □ to 50 Ω / □.

[0072] The resistance value (surface resistance) of the transparent conductive layer 20 can be measured by a four-terminal method in accordance with JIS K7194-1994.

[0073] The above-mentioned resistance value (surface resistance) of the transparent conductive layer 20 indicates the initial resistance value before the transparent conductive film 1 (transparent conductive layer 20) is heated.

[0074] The resistivity of the transparent conductive layer 20 is, for example, 1.0×10 -4 Ω cm~10.0×10 -4 Ω cm, preferably 1.0×10 -4 Ω cm~8.0×10 -4 Ω cm, more preferably 1.0×10 -4 Ω cm~6.0×10 -4 Ω cm, more preferably 1.0×10 -4 Ω cm~5.5×10 -4 Ω cm.

[0075] The resistivity of the transparent conductive layer 20 can be obtained by multiplying the resistance value of the transparent conductive layer 20 by the thickness of the transparent conductive layer 20 .

[0076] <Method of manufacturing transparent conductive film> The method for producing a transparent conductive film of the present invention will be described with reference to FIGS. 2A and 2B.

[0077] First, as shown in FIG. 2A, a transparent substrate 10 is prepared (preparation step).

[0078] Next, as shown in FIG. 2B, a transparent conductive layer 20 is formed on one surface in the thickness direction of the transparent substrate 10 (transparent conductive layer forming step). The transparent conductive layer 20 is amorphous. The transparent conductive layer 20 does not become crystalline even when heated. Specifically, the transparent conductive layer 20 remains amorphous even after the formed transparent conductive film 1 is heat-treated under heating conditions of 140° C. for 30 minutes.

[0079] Specifically, in the transparent conductive layer forming step, a conductive oxide film is formed on one surface in the thickness direction of the transparent substrate 10 by sputtering to form an amorphous transparent conductive layer 20.

[0080] In the sputtering method, a sputtering film forming apparatus is used. The sputtering film forming apparatus can perform the film forming process by a roll-to-roll method. In the transparent conductive layer forming process, a long transparent substrate 10 is used as a work film and is run from a pay-out roll to a take-up roll while a material is formed on one surface in the thickness direction of the transparent substrate 10 to form a transparent conductive layer. The running speed of the work film (transparent substrate 10) is, for example, 0.5 m / min to 10.0 m / min.

[0081] In addition, in the sputtering method, a sputter deposition apparatus having one deposition chamber may be used, or a sputter deposition apparatus having multiple deposition chambers arranged in sequence along the traveling path of the work film (transparent substrate 10) may be used.

[0082] Specifically, in the sputtering method, a sputtering gas (inert gas) is introduced under vacuum conditions into a deposition chamber of a sputter deposition apparatus, while a negative voltage is applied to a target placed on a cathode in the deposition chamber. This generates a glow discharge to ionize gas atoms, and the gas ions collide with the target surface at high speed to eject target material from the target surface, and the ejected target material is deposited on one side of the work film (transparent substrate 10) in the thickness direction. For example, the above-mentioned sintered conductive oxide is used as the target material.

[0083] Examples of the sputtering gas include argon, krypton, xenon, and a mixture of these gases, and preferably argon. The sputtering method is preferably a reactive sputtering method. In the reactive sputtering method, for example, oxygen as a reactive gas is introduced into the deposition chamber in addition to the sputtering gas.

[0084] The ultimate vacuum in the deposition chamber before sputtering is, for example, 1.5×10 -4 Pa or less.

[0085] In the reactive sputtering method, the ratio of the amount of oxygen introduced to the total amount of sputtering gas and oxygen (reactive gas) introduced into the film formation chamber is, for example, 0.5 flow% to 8.0 flow%, preferably 1.0 flow% to 6.0 flow%, and more preferably 2 flow% to 4.0 flow%.

[0086] The film formation temperature (the temperature of the transparent substrate 10 when the transparent conductive layer 20 is formed) is, for example, -50.0°C to 30.0°C, preferably -30.0°C to 20.0°C, more preferably -20.0°C to 10.0°C, and even more preferably -15.0°C to 0.0°C.

[0087] The pressure in the film formation chamber (the pressure in the film formation chamber when the sputtering gas and oxygen are introduced) is, for example, 0.1 Pa to 1.0 Pa, preferably 0.1 Pa to 0.8 Pa, and more preferably 0.2 Pa to 0.6 Pa.

[0088] By adjusting the ultimate vacuum level, the ratio of oxygen introduction, the film formation temperature, and the air pressure during film formation in the transparent conductive layer formation process, it is possible to form a transparent conductive layer 20 that maintains its amorphous nature after heating.

[0089] In the transparent conductive layer forming process, examples of the power source for applying a voltage to the target include a DC power source, an AC power source, an MF power source, and an RF power source. The power source may be a combination of a DC power source and an RF power source. The power source is preferably a DC power source.

[0090] The horizontal magnetic field strength on the target is, for example, 10 mT to 100 mT.

[0091] In this manner, the transparent conductive film 1 is manufactured.

[0092] The transparent conductive film 1 has a thickness of, for example, 20 μm to 500 μm, preferably 50 μm to 400 μm, more preferably 100 μm to 300 μm, still more preferably 130 μm to 250 μm, and particularly preferably 150 μm to 200 μm.

[0093] The transparent conductive film 1 has a total light transmittance (JIS K 7375-2008) of, for example, 60% to 100%, preferably 80% to 100%, more preferably 85% to 100%, and still more preferably 88% to 100%.

[0094] When the total light transmittance of the transparent conductive film 1 is within the above range, the transparent conductive film 1 has excellent transparency.

[0095] After the transparent conductive film 1 is heat-treated under the heating conditions described below, the thermal shrinkage rate in the first direction is 0.40% or more, preferably 0.45% or more, more preferably 0.48% or more, even more preferably 0.50% or more, particularly preferably 0.52% or more, and most preferably 0.54% or more.

[0096] The thermal shrinkage rate in the first direction after the transparent conductive film 1 is heat-treated under the heating conditions described below. However, when the thickness is equal to or greater than the above lower limit, the flexibility after heating is excellent.

[0097] After the transparent conductive film 1 is heat-treated under the heating conditions described below, the thermal shrinkage rate in the first direction is less than 1.50%, preferably 1.20% or less, more preferably 1.00% or less, even more preferably 0.80% or less, particularly preferably 0.60% or less, and most preferably 0.55% or less.

[0098] The thermal shrinkage rate in the first direction after the transparent conductive film 1 is heat-treated under the heating conditions described below. However, when it is equal to or less than the above upper limit, the transparent conductive film 1 (transparent substrate 10) can be prevented from shrinking excessively due to heating, and therefore the occurrence of cracks in the transparent conductive layer 20 can be prevented, and furthermore, curling of the transparent conductive film 1 can be prevented.

[0099] The thermal shrinkage rate in the first direction of the transparent conductive film 1 after heat treatment under the heating conditions described below is 0.40% to 1.50%, preferably 0.45% to 1.20%, more preferably 0.48% to 1.00%, even more preferably 0.50% to 0.80%, particularly preferably 0.52% to 0.60%, and most preferably 0.54% to 0.55%.

[0100] The heat shrinkage rate of the transparent conductive film 1 in the first direction can be measured by the method described in the Examples described later. The heating conditions for measuring the heat shrinkage rate of the transparent conductive film 1 in the first direction are 140° C. and 30 minutes.

[0101] The transparent conductive film 1 has improved flexibility after heating compared to the flexibility before heating. Specifically, the transparent conductive film 1 has a 180° bend diameter (mmφ) after heating that can be measured by the method described in the Examples, which is smaller than the initial 180° bend diameter (mmφ).

[0102] The initial 180° bending diameter (mmφ) of the transparent conductive film 1 is, for example, 35 mmφ or less, preferably 30 mmφ or less, more preferably 25 mmφ or less, and even more preferably 23 mmφ or less.

[0103] When the initial 180° bending diameter (mmφ) of the transparent conductive film 1 is within the above range, the transparent conductive film 1 has excellent bending properties before heating.

[0104] The transparent conductive film 1 has a 180° bent diameter (mmφ) after heating of, for example, 30 mmφ or less, preferably 25 mmφ or less, more preferably 20 mmφ or less, and further preferably 18 mmφ or less.

[0105] When the 180° bent diameter (mmφ) of the transparent conductive film 1 after heating is within the above range, the transparent conductive film 1 has excellent bendability after heating.

[0106] The difference between the initial 180° bend diameter (mmφ) of the transparent conductive film 1 and the 180° bend diameter (mmφ) after heating (initial 180° bend diameter (mmφ) - 180° bend diameter (mmφ) after heating) is, for example, more than 0 mmφ, preferably 1 mmφ or more, more preferably 2 mmφ or more, even more preferably 3 mmφ or more, and particularly preferably 4 mmφ or more.

[0107] When the difference between the initial 180° bend diameter (mmφ) of the transparent conductive film 1 and the 180° bend diameter (mmφ) after heating (initial 180° bend diameter (mmφ) - 180° bend diameter (mmφ) after heating) is within the above range, the flexibility after heating is improved compared to the flexibility before heating.

[0108] The initial 180° bend diameter (mmφ) and the 180° bend diameter (mmφ) after heating of the transparent conductive film 1 can be measured by the method described in the Examples below. The heating conditions for measuring the 180° bend diameter (mmφ) after heating of the transparent conductive film 1 are 140°C and 30 minutes.

[0109] The transparent conductive layer 20 in the transparent conductive film 1 may be patterned. The transparent conductive layer 20 can be patterned by etching the transparent conductive layer 20 through a predetermined etching mask. The patterned transparent conductive layer 20 is, for example, a wiring pattern.

[0110] <Application> The transparent conductive film 1 is included in, for example, a touch sensor, a light control element, a photoelectric conversion element, a heat ray control member, an antenna member, an electromagnetic wave shielding member, a heater member, a lighting device, and an image display device.

[0111] <Action and effect> The transparent conductive film 1 of the present invention has a low resistance because the transparent conductive layer 20 has a thickness of 100 nm or more. In addition, the transparent conductive layer 20 after the transparent conductive film is heat-treated at 140° C. for 30 minutes is amorphous, so that the flexibility after heating is improved compared to the flexibility before heating. Furthermore, the transparent conductive film 1 has a heat shrinkage rate in the first direction of 0.40% or more and less than 1.50% after heat treatment at 140° C. for 30 minutes, so that the flexibility after heating is excellent. EXAMPLES

[0112] The present invention will be described in more detail below with reference to examples and comparative examples. The present invention is not limited to the examples and comparative examples. The specific numerical values ​​of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit (a numerical value defined as "not more than" or "less than") or lower limit (a numerical value defined as "not less than" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention".

[0113] Example 1 First, a roll of a long polyethylene terephthalate (PET) film (product name "T917E188", thickness 188 μm, biaxially stretched film, manufactured by Mitsubishi Chemical Corporation) was prepared as a transparent substrate (preparation step). The PET film had a predetermined length and a width of 1500 mm.

[0114] Next, a 125 nm thick transparent conductive layer was formed on one surface (first surface) of the transparent substrate in the thickness direction by reactive sputtering (transparent conductive layer formation process). In this process, a roll-to-roll sputter deposition device (DC magnetron sputter deposition device) was used. The device is equipped with a deposition chamber that can perform the deposition process while running a work film (transparent substrate) by the roll-to-roll method. The sputter deposition conditions in this process are as follows:

[0115] The ultimate vacuum level in the deposition chamber of the sputter deposition equipment is 0.9×10 -4 After evacuating the chamber to 100 Pa, argon as a sputtering gas and oxygen as a reactive gas were introduced into the film-forming chamber, and the pressure in the film-forming chamber was set to 0.3 Pa. The ratio of the amount of oxygen introduced to the total amount of argon and oxygen introduced into the film-forming chamber was about 3.0 flow rate %. In addition, a sintered body of indium oxide and tin oxide with a tin oxide ratio of 12.5 mass % was used as the target of the sputtering device. A DC power supply was used as the power source for applying a voltage to the target. The horizontal magnetic field strength above the target was 30 mT. The film-forming temperature (the temperature of the transparent substrate on which the transparent conductive layer is formed) was -8°C. The running speed of the PET film as the work film was 5.4 m / min.

[0116] In this manner, a transparent conductive film of Example 1 was produced. The transparent conductive film of Example 1 included a PET film having a thickness of 188 μm and a transparent conductive layer (thickness 125 nm, tin oxide ratio 12.5 mass %) made of an amorphous indium tin composite oxide layer on one surface in the thickness direction of the PET film.

[0117] Comparative Example 1 The transparent conductive film of Comparative Example 1 was produced in the same manner as the transparent conductive film of Example 1, except that the heat shrinkage rate in the first direction of the transparent conductive film was different (see Table 1).

[0118] Comparative Example 2 A transparent conductive film of Comparative Example 2 was produced in the same manner as the transparent conductive film of Example 1, except for the following: A roll of a long polyethylene terephthalate (PET) film (product name "T910E125", thickness 125 μm, biaxially stretched film, manufactured by Mitsubishi Chemical Corporation) was used as the transparent substrate.

[0119] Comparative Example 3 A transparent conductive film of Comparative Example 3 was produced in the same manner as the transparent conductive film of Example 1, except that the thickness of the transparent conductive layer was 65 nm.

[0120] <Evaluation> [Thickness of transparent conductive layer] The thickness (total thickness) of the transparent conductive layer of each transparent conductive film in Example 1 and Comparative Examples 1 to 3 was measured by observation with a field emission transmission electron microscope (FE-TEM). Specifically, first, a cross-sectional observation sample of each transparent conductive layer in Example 1 and Comparative Examples 1 to 3 was prepared by FIB microsampling. In the FIB microsampling method, an FIB device (product name "FB2200", manufactured by Hitachi) was used, and the acceleration voltage was set to 10 kV. Next, the cross-section of the transparent conductive layer in the cross-sectional observation sample was observed by FE-TEM, and the thickness of the transparent conductive layer was measured in the observed image. In addition, in the observation, an FE-TEM device (product name "JEM-2800", manufactured by JEOL) was used, and the acceleration voltage was set to 200 kV. The results are shown in Table 1.

[0121] [Resistance value] The resistance value of the transparent conductive layer of each of the transparent conductive films in Example 1 and Comparative Examples 1 to 3 was measured. Specifically, the measurement was performed as follows.

[0122] First, a measurement film measuring 100 mm x 50 mm was cut out from the transparent conductive film. Next, the resistance value (surface resistance) of the transparent conductive layer of the measurement film was measured using the four-terminal method in accordance with JIS K7194 (1994). The results are shown in Table 1.

[0123] [Heat shrinkage rate] The thermal shrinkage rate after the heat treatment was examined for each transparent conductive film of Example 1 and Comparative Examples 1 and 2. Specifically, first, three first sample films with a size of 10 cm on the first side and 10 cm on the second side were prepared for each transparent conductive film. Next, the shape of each first sample film was measured by a non-contact CNC image measuring machine (product name "QVACCEL606-PRO", manufactured by Mitutoyo Corporation) (first measurement). Next, each first sample film was heat treated in a hot air oven. In the heat treatment, the heating temperature was 140°C and the heating time was 30 minutes. Next, the shape of each first sample film that was cooled to room temperature after the heat treatment was measured by the non-contact CNC image measuring machine (second measurement). Then, based on the shape data obtained by the first measurement and the shape data obtained by the second measurement, the first direction in which the thermal shrinkage rate due to the heat treatment was maximum was identified. The first side was the side extending in the first direction in which the thermal shrinkage rate due to the above-mentioned heat treatment was the largest, and the second side was the side extending in the thickness direction and in a direction perpendicular to the first direction. The thermal shrinkage rates (%) due to the heat treatment of a total of six first sides in the three first sample films for each transparent conductive film were calculated using the following formula. The average of the thermal shrinkage rates (%) of the six first sides of each transparent conductive film was calculated as the thermal shrinkage rate (%) in the first direction. The results are shown in Table 1.

[0124] Heat shrinkage rate (%) = [(length of first side in first measurement) - (length of first side in second measurement)] / (length of first side in first measurement) x 100

[0125] [Crystalline] For the transparent conductive layer of each of the transparent conductive films in Example 1 and Comparative Examples 1 and 2, the crystallinity before heating (initial crystallinity) and the crystallinity after heating (post-heating crystallinity) were examined as follows.

[0126] First, FE-TEM images were taken of the above cross-sectional observation sample at a magnification of 2 million times (the sample preparation method and observation method were the same as those described above for measuring the thickness of the transparent conductive layer). Next, the initial crystallinity of the transparent conductive layer in the captured image was evaluated. Specifically, the transparent conductive layer in the captured image was evaluated as being amorphous when no lattice fringes (corresponding to the presence of crystal grains) were observed over the entire layer, and was evaluated as being crystalline when lattice fringes were observed over the entire layer. The results are shown in Table 1 as initial crystallinity.

[0127] Next, the above cross-sectional observation samples were heat-treated in a hot air oven. In the heat treatment, the heating temperature was 140°C and the heating time was 30 minutes. After the heat treatment, the temperature of each cross-sectional observation sample was lowered to room temperature, and FE-TEM images were taken at a magnification of 2 million times. In the same manner as above, the crystallinity after heating was evaluated for the transparent conductive layer in the captured images. The results are shown in Table 1.

[0128] [Flexibility] The flexibility before and after heating was examined by the following bending test for the transparent conductive layer of each of the transparent conductive films of Example 1 and Comparative Examples 1 and 2. The flexibility indicates the resistance to cracking when bent.

[0129] First, a plurality of films (length 20 cm x width 1 cm) were cut out as test samples from each transparent conductive film. Next, as shown in FIG. 3, the test sample 31 was set on a mandrel rod 32 of a predetermined diameter. The sample 31 was bent 180° at the center in the longitudinal direction of the sample 31 so that the transparent conductive layer was located on the outer side of the bend. The ends 31a and 31b in the longitudinal direction of the sample 31 were fixed to a clip device 33. The distance between the ends 31a and 31b was substantially the same as the diameter of the mandrel rod 32. A weight 34 of 1 kg was hung from the clip device 33. The sample 31 was left stationary for 10 seconds in the state shown in FIG. 4 (bending test). Thereafter, the sample 31 was removed from the mandrel rod 32, and the clip device 33 was removed from the sample 31. Then, the transparent conductive layer of the flattened sample 31 was observed with an optical microscope to confirm the presence or absence of cracks in the transparent conductive layer (microscopic observation). Such bending tests and subsequent microscopic observations were performed on multiple samples derived from the same transparent conductive film. That is, multiple bending tests were performed on each transparent conductive film. In the multiple bending tests, the diameter of the mandrel rod 32 was successively reduced by 0.5 mm from 35 mm by replacing the mandrel rod 32. The maximum diameter among the diameters of the mandrel rod 32 in which no cracks were observed in the microscopic observation is shown in Table 1 as the initial 180° bend diameter.

[0130] Again, a number of films (20 cm long x 1 cm wide) were cut out from each transparent conductive film as test samples. The samples were then heat-treated in a hot air oven. In the heat treatment, the heating temperature was 140°C and the heating time was 30 minutes. The samples were cooled to room temperature after the heat treatment, and the presence or absence of cracks in the transparent conductive layer was confirmed in the same manner as above. The maximum diameter among the diameters of the mandrel rod 32 where no cracks were observed is shown in Table 1 as the 180° bend diameter after heating.

[0131] In addition, the smaller the 180° bend diameter, the better the bendability. In other words, the smaller the initial 180° bend diameter, the better the bendability before heating, and the smaller the 180° bend diameter after heating, the better the bendability after heating.

[0132] [Table 1]

[0133] <Consideration> As described above, Example 1, in which the transparent conductive layer had a thickness of 100 nm or more, had a superior resistance value compared to Comparative Example 3, in which the transparent conductive layer had a thickness of less than 100 nm.

[0134] Moreover, Example 1 had excellent flexibility after heating. This is because the heat shrinkage rate in the first direction of the transparent conductive film of Example 1 was relatively large. In contrast, Comparative Example 1 had poor flexibility after heating. This is because the heat shrinkage rate in the first direction of the transparent conductive film of Comparative Example 1 was relatively small.

[0135] Furthermore, in Example 1, the flexibility after heating was improved compared to the flexibility before heating. This is because the transparent conductive layer remained amorphous even after heating, which is advantageous for tensile bending. In contrast, in Comparative Example 2, the flexibility after heating was reduced compared to the flexibility before heating. This is because the transparent conductive layer was crystallized by heating, which is disadvantageous for tensile bending. [Explanation of symbols]

[0136] 1. Transparent conductive film 10 Transparent base material 20 Transparent conductive layer

Claims

1. A transparent conductive film having a first direction in which a thermal shrinkage rate due to a heat treatment under heating conditions of 140° C. for 30 minutes is maximum in a plane direction perpendicular to a thickness direction, A transparent substrate and a transparent conductive layer disposed on one surface of the transparent substrate in a thickness direction, the transparent conductive layer is amorphous, The transparent conductive layer has a thickness of 100 nm or more, the transparent conductive layer after the transparent conductive film is heat-treated under the heating conditions is amorphous; The transparent conductive film has a thermal shrinkage rate in the first direction after the transparent conductive film is heat-treated under the heating conditions, which is 0.40% or more and less than 1.50%.

2. The transparent conductive film according to claim 1 , wherein the transparent conductive layer has a thickness of 300 nm or less.

3. The transparent conductive film according to claim 1 , wherein the transparent substrate is a polyethylene terephthalate film.

4. The transparent conductive film according to any one of claims 1 to 3, wherein the transparent conductive layer contains an indium tin composite oxide.

5. 5. The transparent conductive film according to claim 4, wherein the indium tin composite oxide has a content of tin oxide of 10 mass % or more with respect to a total content of indium oxide and tin oxide.

Citation Information

Patent Citations

  • Transparent conductive film

    JP2017071850A